Pengaruh promosi dan harga terhadap keputusan pembelian pada hotel berbintang tiga di kota palembang - Deyto Honggoriansyah; Pelliyezer Karo Karo; Mustika Permatasari (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2020)
Abstract Palembang City is the capital of South Sumatra Province which has diverse tourism potential in attracting tourists. It cannot be denied that the Asian Games will be held in 2018, contributing to the increasing number of accommodations in the city of Palembang. With the promotion activities carried out by hotel managers as well as offering the best prices for consumers, the determination of purchasing decisions will be easier. This research is a descriptive verification study using explanatory survey methods and the analysis technique used is path analysis. The purpose of this study was to determine the effect of promotions and prices both simultaneously and partially on purchasing decisions at three Three-Star Hotels, namely Santika Radial Palembang, Batiqa Hotel Palembang, and Swarna Dipa Hotels. The relationship between promotion variables on purchasing decisions has a value of 0.988. The relationship between price variables on purchasing decisions has a price value of 0.756. The relationship between promotion and price on purchasing decisions based on the results of this study states have a significant influence on purchasing decisions. Key words: Promotion, Price and Purchasing Decisions